The Effect of Tourist Attractions and Islamic Attributes on Muslim Tourist Visiting Decisions with Destination Image as a Mediating Variable at Tondok Bakaru Tourism Village - Muhammad Akbar; Rita Yunus; Nurfadilah Sindika Sari; Efriza Pahlevi Wulandari; Rizkiani Iskandar (Universitas Alma Ata, 2025)
Introduction: Indonesia has enormous potential in developing halal tourism, yet its implementation faces challenges in regions where Muslims are not the majority, such as Tondok Bakaru Tourism Village in West Sulawesi. Although the village offers stunning natural landscapes and rich cultural heritage, its ability to attract Muslim tourists remains uncertain due to limited Islamic attributes. This study aims to analyze the influence of tourism attractions and Islamic attributes on Muslim tourists’ visiting decisions, with destination image acting as a mediating variable.Methodology: A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through an online questionnaire from 39 Muslim tourists who had previously visited Tondok Bakaru.Results: Findings reveal that Islamic attributes significantly enhance destination image, which in turn positively influences visiting decisions. Conversely, tourism attractions do not directly affect visiting decisions but contribute indirectly by shaping destination image.Conclusion: Islamic attributes and destination image are essential for attracting Muslim tourists to destinations in non-Muslim majority areas. Tourism managers should prioritize improving Islamic facilities such as prayer spaces and halal food availability and develop a Muslim-friendly destination image to strengthen competitiveness in the growing halal tourism industry. These efforts will help position Tondok Bakaru as an inclusive and appealing destination for Muslim travelers.